Assessment of friction and wear as a function of the pressure applied to the CNT-filled silicone rubber nanocomposite pins. (8th February 2023) - Shinde, Avinash Sudam; Siva, I.; Munde, Yashwant; Sankar, Irulappasamy; Sivakumar, D.
This study aims to determine how the incorporation of carbon nanotube (CNT) fillers can enhance the mechanical and tribological properties of silicon rubber (SiR). The nanocomposite is created by combining the materials in a three-roll mill, compressing the mixture at 170°C, and then curing it for four hours at 200°C. The tensile strength improves by up to 3% for every 0% to 7% increase in the CNT weight percentage, after which it remains constant. When the load is 3% CNT, the coefficient of friction (COF) is at its lowest, and it declines as the load increases. There is a suggestion that the effect of heat and the aggregation of nanoparticles is responsible for the increase in COF that happens as the fraction of CNTs increases. Researchers found that a change in the sliding velocity affected both the coefficient of friction and the specific wear rate.